Accelerated Healing from Severe Radiation Dermatitis Using Noncontact, Low-frequency Ultrasound-assisted Saline Wash Therapy. (January 2023) - Luu, Yen; Han, Joseph; Owji, Shayan; Kamat, Samir; Luu, Chuc; Ungar, Jonathan; Gulati, Nicholas
ABSTRACT: Radiotherapy (RT) is a modality for cancer management that frequently causes critical injury to tissues adjacent to the targeted cancer site. Acute radiation dermatitis (RD) is one of the most common adverse effects of RT and may lead to secondary infection, disfigurement, and discontinuation of therapy. The authors report the efficacy of a multidisciplinary collaboration between radiation oncology, dermatology, and wound care teams in the management of severe, acute RD. This case report describes the use of noncontact, low-frequency ultrasound (NCLFU)-assisted saline wash therapy leading to accelerated healing of severe RD in an older man treated with RT for scalp squamous cell carcinoma. Although NCLFU-assisted saline wash therapy provides gentle debridement of wound surfaces and has demonstrated efficacy in the management of chronic wounds, the potential role for NCLFU therapy in RD management has not yet been explored.